Building ERP solutions with Microsoft Dynamics NAV : create real-world enterprise solutions with NAV, Cloud and the Microsoft stack /: create real-world enterprise solutions with NAV, Cloud and the Microsoft stack. (2017) - Demiliani, Stefano
No abstract available